RANCANG BANGUN PEMANDU VIRTUAL BERBASIS MOBILE UNTUK MUSEUM LAMPUNG MENGGUNAKAN AUGMENTED REALITY - Ossy Dwi Endah Wulansari; Anie Rose Irawati; deasy kusuma anggraeny (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2014)
The Museum is an institution that served to nurture, protect and also as the repository of historic objects. In Indonesia the Museum looks crowded at certain times such as during school holidays and study tours. The Museum can become a means of learning for these students who do research. Mareover, the information provided in the Museum usually a brief information that is less informative. To provide more detailed information and answer the curiosity of visitors then needed a tour guide. Solutions are developed to improve the services and appeal to the Museum by making use of graphics technology of Augmented Reality (AR). Implementation of AR in the Museum can be used to displays informations about an object as well as a Museum Tour Guide. The results showed that the prototype application helps provide information as a virtual guide for the visitors.